Influencia del analfabetismo de los padres, en el proceso de lecto-escritura de los estudiantes de segundo año de educación general básica en la escuela "Simón Bolívar" en el año lectivo 2020-2021. - Gallo, Marcela C. (2021)
This research work was developed from analysis and observations made at the Simón Bolívar school, located in the historic center of the city of Quito. In the present work it was analyzed how the illiteracy of the parents influences the literacy process in the second-year students of EGB, the parents are illiterate due to poverty or lack of interest of the parents of the same, now in currently, second-year students They are harmed, at this level is where we must strengthen the reading-writing process, from the beginning we must correctly encourage the entire process, and if there is not adequate support from parents, we will not do it We can have an educational process with quality and warmth. The present project was applied through a quantitative and qualitative research since the data obtained were collected and analyzed, which were subjected to mathematical analysis, documentary, field and descriptive research was applied, which allowed to support the research with real facts and authentic. In the research we used techniques such as the observation sheet, the survey and the interview, that were applied to the educational community and allowed the collection of data to carry out the presentation and discussion of results, which allowed to conclude that the illiteracy of the students’ parents influence the reading and writing process.